STUDY ON APPLICATION OF GROUND TO COOL VENTILATION AIR FOR BUILDINGS IN MEDAN CITY - Mulfi Hazwi (Jurnal Dinamis, 2011)
AbstractIn tropical countries such as Indonesia, fans or blowers are usually used to circulate air inrooms for better comfortableness. With less ventilation air, this effort, however, releases heatinto the rooms and after a certain time make the rooms becoming uncomfortable. As a fact, forIndonesian climate, temperature of soil under the ground is stable and lower than theatmosphere, especially during day. This paper investigates the application of the ground coolingventilation air for buildings. In order to get the accurate data, temperatures of the soils under theground from 1 m to 7 m deeps aroud the Mechanical Engineering Department of Kampus USUMedan are measured and collected in every minute for 3 months. In the same timetemperatures of the ambient air are also measured and collected in every minute. Themeasurement results show that temperatures of soil are lower than the ambient air. However,inthe location of measurement, for soil lower then 4m the temperatures tend to be increasing.Using the measured data, ventilation air cooled by ground is simulated numerically usingComputational Fluid Dynamics (CFD). The results show that average temperature of the room iscooler with ground cooling.Keywords: ground, cooling, sustainable energy, ventilation air